From Screen to Seoul: How Korean Films Inspire Aspirational Travel Intentions Among Young Working Women - Prawira, Mega Fitriani Adiwarna; Susanto, Eko; Gaffar, Vanessa; Ramadhani, Iqlima (Integrasi Sains Media, 2025)
This study examines the influence of Korean film exposure on aspirational travel intention among young Indonesian working women, focusing on the mediating roles of aesthetic appeal, parasocial interaction, and destination image. Drawing on the Stimulus–Organism–Response (S-O-R) framework, the research employs a quantitative, cross-sectional design. It analyzes data from 287 respondents using Partial Least Squares Structural Equation Modeling (PLS-SEM). All hypothesized relationships were statistically supported. Korean film exposure significantly enhances both aesthetic appeal and parasocial interaction. Aesthetic appeal emerges as the dominant predictor of destination image, which in turn has a substantial impact on aspirational travel intention. Although parasocial interaction contributes positively, its effect is comparatively weaker. These findings highlight the dual psychological pathways—visual and emotional—through which media shapes tourism-related perceptions and long-term travel aspirations. The study contributes to the literature on media-induced tourism and offers practical insights for destination marketers and cultural content creators seeking to leverage cinematic narratives in promoting international travel.